Swinging quanta - Bregman, Judith; Polytechnic Institute of Brooklyn (Chicago : International Film Bureau, 1982)
Uses computer animation to present a visualization of solutions for the quantum harmonic oscillator. Eigenfunctions are displayed and combined to construct a gaussian packet having a time-dependent probability amplitude of a classical nature. The functions are arranged in phase space to give a motion picture rendition of the uncertainty principle of the oscillator
Backup available in VHS 1/2 in.
Keywords: Harmonic oscillators; Gaussian processes